SKIN INFECTION PREVENTION EDUCATION FOR STUDENTS OF TANJUNG PASIR AL-AWWABIEN ISLAMIC BOARDING SCHOOL, JAMBI - Husman, Lipinwati; Dewi, Hasna; Hanina, Hanina; Fairuz, Fairuz; Wulandari, Putri Sari (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
Islamic boarding schools are faced health problems with various types of diseases such as skin diseases and TB. Skin diseases can be caused by bacteria, fungi, parasites, which have the potential to be contagious if students does not practice Clean and Healthy Living Behavior (PHBS). For this reason, the community service team from the Faculty of Medicine and Health Sciences, Universitas Jambi provides education regarding PHBS, carries out skin scraping examinations and it’s treatment. PHBS counseling, looking at the level of knowledge from the pretest and posttest results. The objective of this study is to increase knowledge regarding PHBS prevention of skin infections among students at the Tanjung Pasir Al-Awwabien Islamic Boarding School, Jambi. The implementation of community service activities on Sunday, 11 August 2024 at the Tanjung Pasir Al-Awwabien Jambi Islamic Boarding School. The activity is in the form of PHBS counseling for the prevention of skin infections among students boarding at Islamic boarding schools followed by interactive discussions. The counseling was attended by 135 students aged 10 – 20 years, male and female respondents were 74 and 61 people. The respondent's level of knowledge was measured through a questionnaire twice, pretest and posttest which consisted of 13 questions. The results of data analysis from the questionnaire results obtained an average pretest result of 88.5 and an average posttest result of 97.5. There was an increase in the average value of students knowledge regarding PHBS, even though the score was in the very good category. Interactive counseling can increase students' knowledge, and it is hoped that good PHBS knowledge can be applied in their lives.